Timing of tracheostomy in patients with severe traumatic brain injuries: The need for tailored practice management guidelines. Issue 8 (August 2022) - Selvakumar, Sruthi; Chan, Kelvin; Ngatuvai, Micah; Newsome, Kevin; Ang, Darwin; Bilski, Tracy; Elkbuli, Adel
Abstract: Introduction: Traumatic brain injury (TBI) is one of the leading causes of fatal trauma, and patients often require prolonged ventilation and tracheostomy. There are currently no standardized guidelines regarding the optimal timing of tracheostomy placement for mechanically ventilated patients with severe TBI. This review aims to investigate the impact of tracheostomy timing on the clinical outcomes in patients with severe TBI. Methods: A literature search was conducted according to PRISMA 2020 guidelines. PubMed, Google Scholar, EMBASE, MedLine, Web of Science, Cochrane, and CINAHL were searched for studies evaluating the impact of early versus late tracheostomy on TBI patient outcomes. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) and Newcastle-Ottawa Scale (NOS) were used for quality of evidence and risk of bias assessment, respectively. Results: A total of nine studies met eligibility criteria. All nine studies investigated tracheostomy timing in severe TBI patients and demonstrated that early tracheostomy is associated with decreased ICU length-of-stay (LOS) and increased ventilator free-days compared to late tracheostomy. Conclusion: Current evidence suggests that patients with severe TBI following traumatic injury may benefit from an early tracheostomy due to improved clinical outcomes, including decreased MV duration and ICU-LOS, compared to late tracheostomy. Further multi-institutional studies are needed to develop evidence-based guidelines.